2015
DOI: 10.1074/jbc.m114.619668
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3β-mediated Phosphorylation in the Most C-terminal Region of Protein Interacting with C Kinase 1 (PICK1) Regulates the Binding of PICK1 to Glutamate Receptor Subunit GluA2

Abstract: Background: Despite extensive research, the mechanisms regulating the interaction between protein interacting with C kinase 1 (PICK1) and GluA2 are still unclear. Results: Glycogen synthase kinase-3␤ (GSK-3␤) phosphorylates PICK1. Phosphorylated PICK1 binds to GluA2. Conclusion: GSK-3␤ regulates the GluA2-PICK1 interaction. Significance: This study contributes to our understanding of the mechanisms of long-term depression, an Alzheimer diseaserelated event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…Tau is localized in postsynapse, and is phosphorylated during the removal of GluA2 from synapse [75]. This removal of GluA2 requires interaction between GluA2 and PICK1 [76], which is enhanced by the presence of tau [77]. In the present study, IH28D mice exhibited a decrease in GluA2 and an increase in PICK1 to PSD-95 (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Tau is localized in postsynapse, and is phosphorylated during the removal of GluA2 from synapse [75]. This removal of GluA2 requires interaction between GluA2 and PICK1 [76], which is enhanced by the presence of tau [77]. In the present study, IH28D mice exhibited a decrease in GluA2 and an increase in PICK1 to PSD-95 (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…PICK1 was originally cloned as a protein kinase Cα (PKCα) binding protein found in multiple tissues and organs, most abundantly in the brain, endocrine tissues, and skeletal muscle tissue (Human Proteome atlas). Through the PDZ domain, PICK1 interacts with a number of neurotransmitter receptors, transporters, and enzymes (Figure 7f), where in particular the interactions with the AMPAR [148][149][150][151][152][153][154][155][156][157] and the dopamine transporter (DAT) have received particular attention. Through the PDZ domain, PICK1 interacts with a number of neurotransmitter receptors, transporters, and enzymes (Figure 7f), where in particular the interactions with the AMPAR [148][149][150][151][152][153][154][155][156][157] and the dopamine transporter (DAT) have received particular attention.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
“…Recent studies have shown that NMDAR-induced GSK3 β phosphorylation of tau at Ser-396 is required for hippocampal LTD by enhancing the interaction between the GluA2 subunits of AMPARs with the protein interacting with C-kinase 1 (PICK1) [ 69 , 70 ], a process that is fundamental for AMPAR internalization and/or intracellular retention during LTD [ 71 76 ]. Furthermore, phosphorylation of PICK1 by GSK3 β at Ser-416 has also been reported to augment this interaction [ 77 ].…”
Section: Mechanisms Underlying a β -Inducedmentioning
confidence: 99%